KAJIAN MANAJEMEN RISIKO PROYEK PEMELIHARAAN BERKALA JALAN KREWENG –LEBENG KABUPATEN CILACAP - Basuki & Dwi - & Sri Wiyanti (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2009)
Abstract             Infrastructure development, like  other construction projects, is always overshadowed by the risk of failure. The more big infrastructure projects are handled, the more risk they challenge. Infrastructure projects performers should be able to apply risk management in all projects aspects, including the risks in the construction phase.            At periodic maintenance of road projects in Kreweng – Lebeng, project risks during the construction phase are natural factors / weather, thuggery, licensing, unexpected costs, and coordination with government officials. The strategy for dealing with risk, which is to avoid the risk,  preventing from risk / reduce losses, retain the risk, and transfer the risk.            Various ways of handling that may be conducted at periodic maintenance of road projects in Kreweng - Lebeng are request an extension of time if the delay occurs due to natural factors, complete the safety equipmet to minimize risk of worker accidents, approaching / coordination with local officials to avoid hooliganism, held meetings with residents and local authorities to synchronize perceptions, price surveys to anticipate price rising, complete data so that the permitting process is not too long, and complete the construction data with a complete laboratory test Key words: Risk Management, Infrastructure, Construction Phase, Cilacap District.